Determinants of Employees Job Satisfaction in Polish Enterprises: Findings of Empirical Studies - LemaÅ„ska-Majdzik, Anna; OkrÄ glicka, MaÅ‚gorzata (Journal of Economics and Behavioral Studies, 2016)
Employees’ job satisfaction is influenced by a number of diverse determinants which are related with the work performed by an employee, depend on individual characteristics of an employee, and result from the features of the environment in which a given organisation is functioning. Job satisfaction affects the functioning of an enterprise, its competitiveness and profitability, and high level of employees’ satisfaction may be a key factor impacting the success of the whole organisation. The aim of the paper is to show which determinants of job satisfaction, and at what level, can be distinguished among employees of Polish enterprises, depending on selected variables. A questionnaire survey conducted in 2015 on a group of 158 enterprises enabled identification of statistical dependences and verification of formulated research hypotheses which defined, among other things: the impact of the determinants of employees’ job satisfaction depending on the age of a company, its size, or period of employment of its employees.